The evaluation of the fibromyalgia patients - A. Alciati; G. Arioli; L. Altomonte; R. Casale; S. Stisi; G. Cassisi; G. Biasi; M. Di Franco; M. Spath; D. Buskila; M. Cazzola; F. Ceccherelli; et al. (PAGEPress Publications, 2011)
Fibromyalgia (FM) is a rheumatic disease characterized by musculoskeletal pain, chronic diffuse tension and/or stiffness from joints and muscles, easy fatigue, sleep and emotional disturbances, and pressure pain sensitivity in at least 11 of 18 tender points (TP) (1, 2). This disease has an incidence of 2% in the general population, but it is found more often in middle-aged women (3.4%) (3, 4). The etiopathogenesis of FM has not been clarified yet. FM patients have a dysregulation of pain neurotransmitters and neurohormone-mediated association with irregularities in the physiology of sleep...